The Influence of Electrolytic Concentration on the Electrochemical Deposition of Calcium Phosphate Coating on a Direct Laser Metal Forming Surface - Qianyue Sun; Yuhui Yang; Wenjing Luo; Jinghui Zhao; Yanmin Zhou (International Journal of Analytical Chemistry)
A calcium phosphate (CaP) coating on titanium surface enhances its biocompatibility, thus facilitating osteoconduction and osteoinduction with the inorganic phase of the human bone. Electrochemical deposition has been suggested as an effective means of fabricating CaP coatings on porous surface. The purpose of this study was to develop CaP coatings on a direct laser metal forming implant using electrochemical deposition and to investigate the effect of electrolytic concentration on the coating’s morphology and structure by X-ray diffraction, scanning electron microscopy, water contact angle analysis, and Fourier transform infrared spectroscopy. In group 10−2, coatings were rich in dicalcium phosphate, characterized to be thick, layered, and disordered plates. In contrast, in groups 10−3 and 10−4, the relatively thin and well-ordered coatings predominantly consisted of granular hydroxyapatite. Further, the hydrophilicity and cell affinity were improved as electrolytic concentration increased. In particular, the cells cultured in group 10−3 appeared to have spindle morphology with thick pseudopodia on CaP coatings; these spindles and pseudopodia strongly adhered to the rough and porous surface. By analyzing and evaluating the surface properties, we provided further knowledge on the electrolytic concentration effect, which will be critical for improving CaP coated Ti implants in the future.